Dapagliflozin alleviates renal inflammation and protects against diabetic kidney diseases, both dependent and independent of blood glucose levels - Cai, Anxiang; Shen, Jianxiao; Yang, Xiaoqian; Shao, Xinghua; Gu, Leyi; Mou, Shan; Che, Xiajing (Frontiers in Immunology, 2023)
Diabetic kidney disease (DKD) has become the leading cause of end-stage renal disease worldwide. Therefore, efforts to understand DKD pathophysiology and prevent its development at the early phase are highly warranted. Here, we analyzed kidneys from healthy mice, diabetic mice, and diabetic mice treated with the sodium-glucose cotransporter 2 inhibitor dapagliflozin. Our combined method of ATAC and RNA sequencing revealed Csf2rb, Btla, and Isg15 as the key candidate genes associated with hyperglycemia, azotemia, and albuminuria. Their protein levels were altered together with multiple other inflammatory cytokines in the diabetic kidney, which was alleviated by dapagliflozin treatment. Cell culture of immortalized renal tubular cells and macrophages unraveled that dapagliflozin could directly effect on these cells in vitro as an anti-inflammatory agent independent of glucose concentrations. We further proved that dapagliflozin attenuated ischemia/reperfusion-induced chronic kidney injury and renal inflammation in mice. Overall, our data emphasize the importance of inflammatory factors to the pathogenesis of DKD, and provide valuable mechanistic insights into the renoprotective role of dapagliflozin.